Association of TCTP with Centrosome and Microtubules - Mariusz K. Jaglarz; Franck Bazile; Katarzyna Laskowska; Zbigniew Polanski; Franck Chesnel; Ewa Borsuk; Malgorzata Kloc; Jacek Z. Kubiak (Biochemistry Research International)
Translationally Controlled Tumour Protein (TCTP) associates with microtubules (MT), however, the details of this association are unknown. Here we analyze the relationship of TCTP with MTs and centrosomes in Xenopus laevis and mammalian cells using immunofluorescence, tagged TCTP expression and immunoelectron microscopy. We show that TCTP associates both with MTs and centrosomes at spindle poles when detected by species-specific antibodies and by Myc-XlTCTP expression in Xenopus and mammalian cells. However, when the antibodies against XlTCTP were used in mammalian cells, TCTP was detected exclusively in the centrosomes. These results suggest that a distinct pool of TCTP may be specific for, and associate with, the centrosomes. Double labelling for TCTP and γ-tubulin with immuno-gold electron microscopy in Xenopus laevis oogonia shows localization of TCTP at the periphery of the γ-tubulin-containing pericentriolar material (PCM) enveloping the centriole. TCTP localizes in the close vicinity of, but not directly on the MTs in Xenopus ovary suggesting that this association requires unidentified linker proteins. Thus, we show for the first time: (1) the association of TCTP with centrosomes, (2) peripheral localization of TCTP in relation to the centriole and the γ-tubulin-containing PCM within the centrosome, and (3) the indirect association of TCTP with MTs.